Post-harvest technology of spices: pre-treatments, ouring, cleaning, grading and packing - PRUTHI, J S (Journal of Spices and Aromatic Crops, 1992)
The post harvest technology of spices comprises of a whole gamut of operations such as pretreatments, chemical treatments, curing and similar operations, drying, cleaning, sorting, grading and packing. These aspects are briefly covered in this review. Wherever applicable the problems involved and the relative advantages and disadvantages of the various processes are indicated.